Rescue mission : secret child - Winters, Danica (Harlequin intrigue, 2021)
The moment his ex-fiancée tells him that he's a father, military contractor Mike Spade is ready to make the commitment he's always feared. Intelligence operative Summer Daniels is willing to give him another chance. Then their child is abducted. Mike and Summer both have enemies--and they both have unhealed hurts from their tempestuous romance. Can they overcome the past to save their son?